Penerapan SNI 03-7051-2004 (pemberian Tanda dan Pemasangan Lampu Halangan (Obstacle Lights) di Sekitar Bandara) di Bandara Juanda Surabaya - Yati Nurhayati (Research and Development Agency of The Ministry of Transportation, 2011)
Assessment of the Implementation of SNI 03-7051-2004 (The Signs And Installation of Obstruction Lights (Obstacle Lights) vicinity at Airport) For Compulsory Standards at Juanda Airport in Surabaya is to know how the implementation of the provision of signs and installation of lights around the aviation operation Safety area at Juanda Airport Surabaya to support it has required the standards/rules established by the Directorate General of Civil Aviation flight operations in order to ensure aviation safety. Assessment method used quantitative method by decomposition (descriptive), exposure and a detailed explanation based on the compilation of primary data and secondary data that have been processed. The assessment result shows the application of SNI 03-7051-2004 (The Signs and Installation of Obstruction Lights of Airport vacinity at Juanda Airport) vacinit at Surabaya there are still some buildings that do not meet the rules set, there are some buildings should be installed (obstacle lights) to achieve optimum aviation safety. Among these buildings are of BTS Tower buildings and Mall City Of Tomorrow (Cito Mall) that located at the aviation operation area at Juanda airport.